PELATIHAN PEMBUATAN ALAT PERMAINAN EDUKATIF (APE) BAGI GURU TK SAHABAT MENTARI - Hevie Setia Gunawan; Dindin Sopyan Abdulah (Jurnal Al Maesarah, 2023)
This Community Service (PkM) is motivated by a problem with teachers' creative abilities in developing Educational Game Tools (APE) as well as the limited game tools that teachers can use and use for the learning process, this makes children bored and less enthusiastic. Participate in various activities in class. The aim of Community Service (PkM) activities which are carried out in the form of training activities is so that teachers at Sahabat Mentari Kindergarten can develop their abilities in making educational game tools (APE) creatively, using simple materials sourced from used materials found around them. The method used is in the form of training activities for Friends of Mentari Kindergarten teachers on how to make educational game tools (APE). Next, an evaluation process is carried out to find out the extent of the obstacles and various shortcomings in the implementation of activities so that later improvements can be made. As the final result of this activity, it is hoped that every teacher will have interesting and creative learning media by relying on materials that are easy to make so that they can support the learning process.